A critical analysis of the manifestation of patriarchal power relations in Zimbabwe’s urban groove music. - Keche, Kudakwashe; Manatsa, Proceed (Scientific Journals International, 2016)
This article analyzes how patriarchal power relations have evolved and manifested through Zimbabwean Urban Groove music. We will explore the extent to which the urban groove musical genre reproduces dominant, patriarchal power relations through the discourse of popular culture paying particular attention to findings by scholars such as Stuart Hall, John Fiske, among others. The paper will also show how patriarchal power relations appear as mystical and religious connotations as it turns its attention from exotic to mundane and from indigenous to authored culture.